2013
DOI: 10.1186/cc13150
|View full text |Cite
|
Sign up to set email alerts
|

Decreased HLA-DR antigen-associated invariant chain (CD74) mRNA expression predicts mortality after septic shock

Abstract: IntroductionSeptic syndromes remain the leading cause of mortality in intensive care units (ICU). Septic patients rapidly develop immune dysfunctions, the intensity and duration of which have been linked with deleterious outcomes. Decreased mRNA expressions of major histocompatibility complex (MHC) class II-related genes have been reported after sepsis. We investigated whether their mRNA levels in whole blood could predict mortality in septic shock patients.MethodsA total of 93 septic shock patients were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
63
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 19 publications
9
63
1
1
Order By: Relevance
“…sCD74 also may act as a biomarker for burn-related sepsis. In contrast to our findings, Cazalis et al reported decreased mRNA levels of CD74 in septic shock patients and an association with increased risk of mortality [23]. This apparent contradiction may be explained by the dynamics of soluble factors which depend on the underlying insult.…”
Section: Discussioncontrasting
confidence: 99%
“…sCD74 also may act as a biomarker for burn-related sepsis. In contrast to our findings, Cazalis et al reported decreased mRNA levels of CD74 in septic shock patients and an association with increased risk of mortality [23]. This apparent contradiction may be explained by the dynamics of soluble factors which depend on the underlying insult.…”
Section: Discussioncontrasting
confidence: 99%
“…Cazalis et al . studied mRNA expression of five different MHC class II related genes, including CD74 ( HLA‐DRA associated invariant chain) and HLA‐DRA , and found CD74 to be the strongest predictor of negative outcomes. However, that study was based on only one sample per patient, collected 3–4 days after onset of septic shock.…”
mentioning
confidence: 99%
“…Low monocyte HLA-DR expression levels serve as a surrogate marker of monocyte "anergy," development of nosocomial infections, and death (48)(49)(50). Several studies correlate low monocyte HLA-DR expression levels with diminished monocyte function and reduced antigen-specific lymphocyte proliferation (51,52), suggesting that monocyte anergy and immune suppression independently contribute to the increased risk of adverse events in sepsis.…”
Section: Introductionmentioning
confidence: 99%